A systematic review and meta-analysis of intraperitoneal anastomosis versus extraperitoneal anastomosis in laparoscopic left colectomy - Wang, Xueting; Dan, Jie; Zhu, Mingjie; Li, Ming; Liu, Ke; Liao, Qian (Frontiers in Oncology, 2024)
BackgroundThe effectiveness of the anastomosis method for laparoscopic left colectomy (LLC) remains inconclusive. Thus, a systematic review and meta-analysis were conducted to compare the outcomes between intraperitoneal anastomosis (IPA) and extraperitoneal anastomosis(EPA)in LLC.MethodsPubMed, Embase, the Cochrane Library, CNKI, and WanFangData were systematically searched for relevant literature. The literature was screened independently by two groups, and data were extracted and evaluated for bias. Meta-analysis was performed using Revman5.4 software.ResultsTwelve studies with a total of 1,278 patients were included in our meta-analysis. Compared with the EPA group, the IPA group had less blood loss [odds ratio (OR)=–20.32, 95% confidence interval (CI) (−27.98–12.65), p<0.00001], a lower overall complication rate [OR=0.45, 95% CI (0.33–0.63), p<0.00001], fewer non-severe complications [OR=0.44, 95% CI (0.30–0.64), p<0.0001], and fewer surgical site infections [OR=0.39, 95% CI (0.21–0.71), p=0.002]. Additionally, a longer operation time appeared in the multicenter and propensity score matching (PSM) subgroups of the IPA group. Furthermore, patients in the IPA group had an earlier exhaust time and shorter hospital stays. There were no significant differences between the two groups regarding severe complications, anastomose-related complications, postoperative blood transfusion, ileus, reoperation rate, time to stool, pathologic sample length, and lymph node dissection number.ConclusionIPA seems more advantageous than EPA for patients receiving LCC in terms of complications and postoperative recovery and has similar oncological outcomes. However, it may take longer and be more difficult to perform.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/#recordDetails PROSPERO, identifier (CRD4202454391).